Survey and Effects of Weather Parameters on Powdery Mildew of Black Gram Caused by Erysiphe Polygoni DC - Meena, Sakshi; Meena, Mahendra Kumar; Bunker, R.N. (International Journal of Environment, Agriculture and Biotechnology, 2024)
Surveys were conducted during kharif 2018 in ten villages viz., Gandholi, Noorda, Joonawas, Odwariya, Banora, Malpur, Panarwa, Oda, Khandiovri and Sundara of four tehsil’s (Mavli, Salumbar, Jhadol and Kherwara) of Udaipur district. The maximum (54.67%) disease incidence was recorded in Joonawas village (Mavli tehsil) with 43.22% disease severity while, minimum incidence 25.40% with 19.54% severity from Malpur village (Salumber tehsil). Study of weather parameters in relation to powdery mildew development revealed that, the maximum disease severity (8.67-58%) was found during July 30- Sept 2, 2018. During this period the maximum temperature (29.1-30.5˚c), minimum temperature (22-22.9˚c), maximum relative humidity (82.6-85.1%), minimum relative humidity (58.6-78.3%), sunshine (1.2-3.6 hours) and rainfall (17.4-67.6 mm) was favoured for powdery mildew development.